2020
DOI: 10.3390/ijerph17030733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Fundamental Motor Skill-Based Afterschool Program on Children’s Physical and Cognitive Health Outcomes

Abstract: Globally, more than half of school-aged children do not engage in the recommended 60 minutes of daily moderate to vigorous physical activity (MVPA). Given that developing sufficient fundamental motor skills (FMS) competence during early elementary school years is important for a child’s physical and cognitive development, the purpose of this study was to examine the effects of an 8-week FMS-based afterschool program on physical and cognitive health outcomes among elementary children. Participants were 31 K–2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 53 publications
4
49
0
Order By: Relevance
“…(2) Combine more free play time and directed PE during the school day since the time of motor experiences is a determining factor in the development of motor competence [31]. 3Implement programs based on FMS in other school settings, such as during recess and breaks in the classroom [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Combine more free play time and directed PE during the school day since the time of motor experiences is a determining factor in the development of motor competence [31]. 3Implement programs based on FMS in other school settings, such as during recess and breaks in the classroom [28].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we must not forget that the development of motor competence in boys and girls is one of the objectives of PE [22,23], and the development of motor competence is considered a critical element within a quality PE class since it provides an inclusive, qualified and meaningful opportunity for all children [24]. For these reasons, motor competence has become one of the most important contents to work on in compulsory schooling [25,26], as included in the study plans designed by educational administrations [23], because the development of each child is of special importance to them since motor skills are essential for their integral development [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Afterschool programs can be efficacious for implementing jump rope exercise since they allow students to participate in a variety of movements and physical activities [ 27 , 28 ]. Previous evidence has shown that an afterschool PA program brings multiple health benefits, including increased PA behaviors [ 29 ], working memory [ 30 ], motor skills competence [ 31 ], reduced body fat [ 32 ], and increased academic motivation and effort [ 33 ]. It was also noted that adolescents’ MVPA was strongly associated with supervised PA and accessibility to sports equipment and facilities during afterschool programs [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these challenges, it has been suggested that the higher physical activity levels observed for active play may also improve FMS for preschool and school-aged children (Engelen et al, 2013;Adamo et al, 2016;Johnstone et. al., 2017;Foulkes et al, 2017;Lee et al, 2020). Although the positive interaction between PA levels and FMS proficiency proposed for active play seems plausible, the effect and benefits of active play programs on increased PA levels and improved FMS remains unclear (Johnstone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%